A Cost Analysis of Hospitalization for Vaginal and Cesarean Deliveries [282]. (May 2015) - Shah, Neel T.; Golen, Toni Huebscher; Kim, Julia G.; Mistry, Bipin; Kaplan, Robert; Gawande, Atul
Abstract : INTRODUCTION: The American College of Obstetricians and Gynecologists has called for safely reducing cesarean delivery rates and policymakers have proposed linking cesarean delivery rates to value-based insurance designs. Predicting the effect of reducing cesarean delivery on institutional margins is complex because the costs are rooted in the clinical processes of care. We aimed to compare how in-hospital costs accrue during different steps of the clinical care processes for vaginal and cesarean deliveries. METHODS: Traditional hospital cost accounting does not allocate costs to the discrete steps of clinical care processes. We used time-driven activity-based costing to uncover how costs and care are linked for vaginal and cesarean deliveries. We abstracted financial records from the business decision support unit of Beth Israel Deaconess Medical Center to assign per-minute capacity cost rates to hospital resources. Clinical processes for each mode of delivery were mapped in detail from admission to discharge. The time, personnel, location, and capital associated with each clinical step of care were documented. Clinical processes were validated through direct observations. One-way sensitivity analysis was performed on the time parameters. RESULTS: Processes that take place on the labor floor are highly resource-intensive as a result of the level and number of personnel required, whereas postpartum processes are less resource-intensive. On average, vaginal deliveries require more than 700% more labor floor time compared with cesarean deliveries. Within the bounds of our sensitivity analyses, we found that vaginal deliveries are approximately 200% more expensive than cesarean deliveries until the birth takes place and cost equivalent to cesarean deliveries when summed over the entire length of stay. CONCLUSION AND IMPLICATION: Payment reforms may not influence outcomes without financial incentives to improve process efficiency for vaginal deliveries.